Kepercayaan Publik kepada Pemerintah Daerah Pasca Orde Baru - Ulber Silalahi (Universitas Riau, 2011)
Public trust in government is important because trust is social capital in governancesystem as such as relationship between government and businessman. The problems which arefaced by many government as such as Indonesia in this decade are the decline of public trust intheir government. This study is to explain the degree of businessman trust in Bandung CityGovernment in business licence service delivery. This study based on descriptive-quantitativemethods. Sample size are 100 businessman who were selected by nonprobability sampling withquota sampling technic. Sample were sampled from member of KADIN Bandung who applyed forbusiness license in 2001-2005. Research used survey design with questioner and interview as aprimary research instrumnet to collect data. The data were analyzed using descriptive statisticwith central tendency. Results of this study show that businessman trust in Bandung City Gov-ernment is low or distrusting. Businessman trust is low in local government because bureaucrat oflocal government have low integrity, commitment, concistency and loyality in business lincenceservice delivery.